2001
DOI: 10.1038/35088026
|View full text |Cite
|
Sign up to set email alerts
|

Vacancies in solids and the stability of surface morphology

Abstract: Determining how thermal vacancies are created and destroyed in solids is crucial for understanding many of their physical properties, such as solid-state diffusion. Surfaces are known to be good sources and sinks for bulk vacancies, but directly determining where the exchange between the surface and the bulk occurs is difficult. Here we show that vacancy generation (and annihilation) on the (110) surface of an ordered nickel-aluminium intermetallic alloy does not occur over the entire surface, but only near at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 18 publications
5
69
0
Order By: Relevance
“…The observation of stationary substrate steps suggests that the steps are not a major source of Al atoms in the initial oxidation of NiAl (110), that is, the oxide growth involves Al atoms from another source (i.e., the NiAl bulk). Indeed, McCarty and coworkers (22,23) have shown that mass transport between the NiAl(110) surface and the bulk can be very efficient at elevated temperatures (750-1,000°C). For clean NiAl(110) in vacuum, surface Al atoms supplied from the bulk attach to steps, thus inducing step migration (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of stationary substrate steps suggests that the steps are not a major source of Al atoms in the initial oxidation of NiAl (110), that is, the oxide growth involves Al atoms from another source (i.e., the NiAl bulk). Indeed, McCarty and coworkers (22,23) have shown that mass transport between the NiAl(110) surface and the bulk can be very efficient at elevated temperatures (750-1,000°C). For clean NiAl(110) in vacuum, surface Al atoms supplied from the bulk attach to steps, thus inducing step migration (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, McCarty and coworkers (22,23) have shown that mass transport between the NiAl(110) surface and the bulk can be very efficient at elevated temperatures (750-1,000°C). For clean NiAl(110) in vacuum, surface Al atoms supplied from the bulk attach to steps, thus inducing step migration (22,23). However, under oxidizing conditions it is thermodynamically more favorable for Al atoms supplied from the bulk to be incorporated in the growing oxide rather than steps.…”
Section: Resultsmentioning
confidence: 99%
“…One example is the diffusion of transition metal atoms into bulk Si, which may actually be more efficient than diffusion on the surface [1]. Surface morphology changes mediated by bulk vacancy transport [2] and vacancy mediated surface diffusion [3] have also been discussed recently for metals. In this Letter, we discuss a growth mechanism in which the surface transport involves adatom diffusion below a metallic adlayer on a semiconductor surface.…”
mentioning
confidence: 99%
“…In case the observed decay of Ga droplets is due to diffusion of Ga into the bulk of the sample or evaporation into vacuum, all of the droplets would decrease in size. [33][34][35][36] We find that droplets B-I exhibit decay while the size of droplet A remains nearly constant at all t. Moreover, the rates of changes in droplet size are not the same for all the droplets. For example, the sizes of smaller droplets F and G decrease continuously, while the sizes of larger droplets B and C change little initially and decrease at later times.…”
Section: Fig 2 Typical Bright-field Xtemmentioning
confidence: 76%